Global research status and hot trends in stem cells therapy for Intervertebral disc degeneration: A bibliometric and clinical study analysis - Wang, Nan; Chen, Shuang; Zhang, Xiaoyu; Xi, Zhipeng; Fang, Xiaoyang; Xue, Congyang; Li, Jingchi; Xie, Lin (Frontiers in Pharmacology, 2022)
Background: Stem cells(SCs) therapy for intervertebral disc degeneration(IDD) has been studied for nearly 20 years and it is an important part of regenerative medicine and tissue engineering research, as well as a current research hotspot and challenge. Although the volume of literature has shown an annual growth trend, there is no literature available for bibliometric and clinical analysis of the content of multiple databases in this field. Methods: The articles were obtained from the WOSCC, Scopus, Pubmed and ClinicalTrials on December 27, 2021. Three scientometric software (VOSviewer 1.6.17, CiteSpace 5.8.R.1 and Scimago Graphica) were used to perform bibliometric and knowledge-map analysis. Results: We included 867 articles from WOSCC, 716 articles from Scopus and 6 clinical studies from ClinicalTrials for literature analysis. Our results showed that China was the country with the highest number of publications, with the United States(US) being the leader in terms of international collaborations and the number of citations. Sakai D, Grad S and Hoyland JA had made outstanding contributions for their high productivity and the quality articles. Spine was the most published and most cited journal, in addition to Spine Journal and Biomaterials, which were also more authoritative journals and had received high citations. All of them had received high citations. Keyword co-occurrence studies suggested that the current hotspots were in mechanistic studies, including inflammation, apoptosis, exosome, autophagy and others. Some studies had also investigated tissue-engineered scaffolds of SCs to better repair degenerated discs. Clinical studies were relatively scarce. Direct injection of Mesenchymal Stem Cells(MSCs) into degenerated discs for the treatment of Degenerative disc disease(DDD) was the current direction of research. Conclusion: This study demonstrates the global research hotspots, trends and clinical use of SCs in the treatment of IDD. It can help scholars to quickly understand the current status and hot spots of research in this field, and also provide some guidance and reference for those who are currently researching in this area.